Pengaruh Variasi Kecepatan Agitasi pada Produksi Β-Glukan dari Saccharomyces cerevisiae - Laras Cempaka (Al-Kauniyah: Jurnal Biologi, 2015)
β-glucan is very interesting to study because of a variety of benefits that it provides. Saccharomyces cerevisiae is a unicellular yeast which has a β-glucan component of the biggest in the cell wall. This study aimed to describe the effect of agitation speed on the production of β-glucan from S. cerevisiae. Agitation speed plays an important role in cell growth. This research used agitation speed at 80 rpm, 120 rpm and 200 rpm. The research design used was a completely randomized design with three replications. During the fermentation in sixteen hours, several parameters were examined including cell number, pH, glucose and protein of the medium and the crude β-glucan. β-glucan extraction procedures done by adding NaOH 2% solution to the fermented product. Then, the supernatant was neutralized with acetic acid solution. To get the crude deposits of β-glucan, ethanol 96% was added in volume as three times of the supernatant. Production of β-glucan was increas along with the growth of the cell.Data analysis was performed using one way ANOVA test followed by LSD analysis. Production of β-glucan increases with cell growth. pH value, the concentration of carbon source and nitrogen source on the substrate decreased during the fermentation process. β-glucan production also increased as the rising of agitation speed from the 80 rpm until 200 rpm. Rate of β-glucan production in 80 rpm, 120 rpm and 200 rpm were 18.19 μgL-1/ hour, 40.42 μgL-1/ hour, 44.03 μgL-1/ hour, respectively. Based on the experiment results, the most optimum agitation speed for beta-glucan were respectively 200 rpm with beta-glucan content reached 1624.44 µg/L.